Exploring the valuation of compulsory purchase compensation. Issue 2 (6th August 2018) - Holtslag-Broekhof, Sanne; Beunen, Raoul; Marwijk, Ramona Van; Wiskerke, Johannes S.C.
Abstract : Purpose: This paper aims to analyse how Dutch Compulsory Purchase (CP) compensation is decided on and to explore to what extent the valuation of the CP compensation is assessed by professionals within a range of 10 per cent (higher or lower) difference. Design/methodology/approach: The authors study CP compensation using the Dutch Legal Intelligence database, assessing every publicly available court decision and comparing the compensation that is offered in the voluntary negotiations and during the CP procedure in court. Findings: The results show that there are many uncertainties in the valuation process of CP that lead to a broad range of valuation outcomes. In 94 legal CP cases from the Netherlands, the final offer of compensation in court was on average 56.7 per cent higher than the last compensation offer from the expropriator. The differences in valuation were related to several aspects including different systems of valuation and different interpretations of the CP legislation. Originality/value: A central issue in the CP procedure is the amount of compensation that the landowner receives. There are few researchers who have studied how accurate CP compensation is appraised in practise. This is one of the first attempts internationally to empirically conduct an analysis of CP compensation values.